Multimodal MRI study of gray matter and functional connectivity abnormalities in adolescents with bipolar disorder - Zhu, Pengyu; Wang, Yuxi; Xiang, Jialin; Gu, Junchen; Chen, Xiong; Chen, Fang; Zou, Lulu; Ai, Chunqi; Qin, Kun; Chen, Wen (Frontiers in Psychiatry, 2025)
BackgroundAdolescent bipolar disorder (BD) is a severe psychiatric condition characterized by mood instability, with significant impacts on social and cognitive functioning. Clarifying the neural mechanisms underlying BD during adolescence may aid early diagnosis and treatment.MethodsWe conducted a multimodal neuroimaging study integrating functional and structural MRI data to investigate alterations in spontaneous neural activity (amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo)), seed-based resting-state functional connectivity (rsFC), and gray matter volume (GMV) in 69 adolescents with BD and 42 matched healthy controls (HCs). ALFF and ReHo were used to identify local functional abnormalities. Overlapping brain regions were selected as seeds for rsFC analysis. Voxel-based morphometry (VBM) was performed to detect GMV differences. Correlations between imaging measures and clinical symptom scores (HAMD, HAMA, YMRS) were assessed.ResultsCompared to HCs, BD patients exhibited significant abnormalities in the ALFF within the default mode network (DMN) and the salience network (SN). ReHo was also altered in the SN. Seed-based rs-FC analysis revealed reduced connectivity between the right supramarginal gyrus and the left middle frontal gyrus, which are key nodes of the frontoparietal network (FPN). VBM analysis demonstrated decreased GMV in the left cerebellum. No significant correlations were found between imaging measures and clinical scale ratings.ConclusionsOur findings suggest that adolescent BD is characterized by functional abnormalities within DMN and FPN, as well as cerebellar gray matter atrophy. Disrupted structure–function coupling in these regions may reflect possible neurobiological mechanisms underlying BD during adolescence.